Comparison for Determination of Potassium Levels in Bananas by Fiber Optic Displacement Sensor and Atomic Absorption Spectroscopy - Muhammad Affendi Muhizan; Nurul Nadia Adnan; Nur Athirah Mohd Taib (Enhanced Knowledge in Sciences and Technology, 2024)
A fiber optic displacement sensor (FODS) operation is based on the intensity modulation technology, which employs a plastic optical fiber-based bundle as a probe and a flat mirror plane as the reflecting surface is demonstrate to assess potassium in bananas. There are many methods developed to obtain more accurate measurement of potassium concentration that requires an instrument with high linearity and sensitivity. Thus, an optical intensity-modulated based sensor composed of He-Ne laser with an output wavelength of 632.8nm developed to determine the concentration of potassium in bananas. Hence, the research observed the comparison of FODS system with one of the conventional methods which is Atomic Absorption Spectroscopy (AAS) which yielding a sensitivity of 0.0000840469 V/mg/L for FODS and 0.0011100000 mg/L for AAS with linearity for both exceeding 99%. The approach method offers a practical solution for assessing potassium level in bananas, real-time monitoring the level of substance in samples, and provide a convenient and high sensitivity system.